Microleakage of Two Composite Resin Materials in Restored Primary Teeth: An In Vitro Study - Daneshyar, Fahimeh; Yadegari, Atiye; Soltanian, Alireza; Tayebi, Soudeh (Journal of Dental School, 2024)
Objectives Restoration of primary teeth have become more critical than extracting them. Composite resin materials are considered suitable materials for primary teeth restoration due to their aesthetic and acceptable performance. However, they have limitations such as polymerization shrinkage, microleakage, post-treatment sensitivity, and reduced marginal adaptation. This study evaluated the microleakage of Tokuyama Bulk flow composite and Grandiflow composite resin materials in restored primary teeth. Methods In this in vitro study, 54 primary teeth were randomly divided into two groups. After preparing the Class II cavity in the samples and applying acid etch and bonding material, one group was allocated to the Tokuyama Bulk flow composite, and the other group was allocated to the Grandiflow composite. The amount of microleakage was determined by immersion of samples in 1% methylene blue dye and evaluation under stereomicroscope. Scores from 0 to 3 were assigned depending on the degree of dye penetration. Mann-Whitney U test was used to compare the scores in two groups at a significance level of 0.05. Results The amount of microleakage in the Grandiflow group was significantly higher than the Tokuyama Bulk flow group (p=0.019). In the Grandiflow group, the highest microleakage score was 3 (63.0%), 2 (29.6%), and 1 (7.4%), respectively. In the Tokuyama Bulk flow group, the highest microleakage scores were 2 (55.6%), 3 (29.6%), 1 (11.1%), and 0 (3.7%), respectively. Conclusion It can be concluded that Tokuyama Bulk flow composites have lower microleakage than the Grandiflow composite, potentially affecting the microleakage and subsequent failure of the restoration in a positive way.